2022
DOI: 10.1177/00219983221133149
|View full text |Cite
|
Sign up to set email alerts
|

An analytical investigation of self-temperature-compensated stretchable piezoresistive nanocomposites containing hybrid carbon black/carbon nanotube nanofillers

Abstract: In this study, the temperature-dependent piezoresistivity of hybrid carbon black (CB)/carbon nanotube (CNT) nanocomposites is studied using a percolation model with a Monte Carlo simulation approach. With this approach, the temperature-dependency of electrical resistivity and the strain sensitivity of the nanocomposite are investigated. In addition, other parameters such as the aspect ratio, dispersion state and dimensions’ effect on piezoresistivity of the compensated stretchable nanocomposite are investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
2
1
Order By: Relevance
“…69 Haghgoo et al came to the same result in their Montecarlo simulation of CB and CNTs in arbitrary matrix. 70 Our results do not fit these predictions (see Figure 6B), as the gauge factor does not increase close to the percolation threshold when the concentration is varied. This might be because the estimation that the particles are distributed evenly in a cubic lattice, does not hold since the particles are applied on fibers and are not distributed 3-dimensionally in the polymer matrix.…”
Section: δRcontrasting
confidence: 61%
See 1 more Smart Citation
“…69 Haghgoo et al came to the same result in their Montecarlo simulation of CB and CNTs in arbitrary matrix. 70 Our results do not fit these predictions (see Figure 6B), as the gauge factor does not increase close to the percolation threshold when the concentration is varied. This might be because the estimation that the particles are distributed evenly in a cubic lattice, does not hold since the particles are applied on fibers and are not distributed 3-dimensionally in the polymer matrix.…”
Section: δRcontrasting
confidence: 61%
“…Zhou et al found that this also applies to CB in polymer matrix: the sensitivity of a piezoresistive sensor increases for smaller carbon black mass fractions 69 . Haghgoo et al came to the same result in their Montecarlo simulation of CB and CNTs in arbitrary matrix 70 . Our results do not fit these predictions (see Figure 6B), as the gauge factor does not increase close to the percolation threshold when the concentration is varied.…”
Section: Resultsmentioning
confidence: 48%
“…Advanced nanocomposites filled by nanoscale particles have attracted much attention from scientists and engineers. [1][2][3][4][5] These nanocomposites have numerous applications in a wide range of temperature sensing elements, actuators, aerospace industry, biological micro-electro-mechanical devices etc. [6][7][8][9][10] Among them, the carbon nanotube (CNT)-reinforced polymer nanocomposite is one of the most popular materials indicating excellent mechanical, thermal and electrical properties at a low level of CNTs.…”
Section: Introductionmentioning
confidence: 99%